Growth of ZnO Nanorod Arrays on Flexible Substrates: Effect of Precursor Solution Concentration. (31st July 2012) - Tong, Fei; Kim, Kyusang; Wang, Yaqi; Thapa, Resham; Sharma, Yogesh; Modic, Aaron; Claude Ahyi, Ayayi; Issacs-Smith, Tamara; Williams, John; Ahn, Hosang; Park, Hyejin; Kim, Dong-Joo; et al.
Abstract : We report a low-temperature aqueous solution growth of uniformly aligned ZnO nanorod arrays on flexible substrates. The substrate is Indium Tin Oxide (ITO) film coated on polyethylene terephthalate (PET). Solutions with five different concentrations of the precursors with equimolar Zinc Nitrate and Hexamethylenetetramine (HMT) in distilled water were prepared to systematically study the effect of precursor solution concentration on the structural and optical properties of ZnO nanorods. It was concluded that the precursor concentration have great influence on the morphology, crystal quality, and optical property of ZnO nanorods. The diameter, density, and orientation of the nanorods are dependent on the precursor solution concentration. X-ray diffraction and micro-Raman spectroscopy showed that the ZnO nanorods with the highest concentration of 50 mM were highly aligned and have the highest level of surface coverage. It was also found that the diameter and length of the nanorods increases upon increasing precursor solution concentration. This is the first systematic investigation of studying the effect of precursor solution concentration on the quality of ZnO nanorods grown on ITO/PET substrates by low-temperature solution method. We believe that our work will contribute to the realization of flexible organic-inorganic hybrid solar cell based on ZnO nanorods and conjugated polymer.